Dynamics of biochemical indicators in the mesocycle of training in highly qualified weightlifters - Sivokhin, I. P.; Mardenova, G. B.; Ogienko, N. A.; Safargalieva, G. N.; Skotnikov, V. F. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study the dynamics of changes in biochemical parameters in the blood of weightlifters and to identify the magnitude and direction of individual changes in biochemical markers within the mesocycle of the training process before and after participation in international competitions.